Caracterização químico-faciológica dos derrames komatiíticos do Grupo Quebra Osso, greenstone belt Rio das Velhas, no setor leste do Quadrilátero Ferrífero/MG - Raianny Carolini Ramos Ferreira (2020)
The Quebra Osso komatiite flow field is part of the 2.9-2.7 Ga Rio das Velhas greenstone belt, in the Quadrilátero Ferrífero province, located in the southern São Francisco craton (Brazil). It is mostly composed of metamorphosed komatiites with minor association of volcaniclastic and metasedimentary rocks (banded iron formations, chert, carbonaceous phyllites and fuchsite-quartz schists). Through new detailed geological mapping and petrography, the komatiite flows were subdivided into coherent (massive, layered and pillowed facies) and autoclastic facies (autobreccias and hyaloclastites), formed by effusive flows; and minor pyroclastic facies (metatuffs and metalapilli-tuffs) that are related to explosive flows. The igneous textures are still preserved in these rocks although their primary minerals (olivine and pyroxene) were completely pseudomorphosed by serpentine and/or chlorite. The greater proportion of the komatiites of Quebra Osso Group is massive and cumulate-textured, which suggests a channelized flow. The layered flows are subordinate and encompass an upper zone of random spinifex that grades to a lower cumulate zone. They are restricted to the marginal zones and interpreted as breakouts of lava from the main pathway. The occurrence of pillow lavas, hyaloclastites and chemical sediments indicates that komatiite lavas have erupted in submarine environment. The abundance of autobreccias suggests a turbulent percolation of komatiites and/or multiple influxes of melts that caused the fragmentation of the solidified lava and magma mixing. The mineral assemblage is secondary and comprises serpentine, chlorite, tremolite and talc, and minor carbonate, rutile and opaques, typical of greenschist to lower amphilolite facies. The Quebra Osso komatiites are mostly classified as Al-enriched and Al-undepleted (Al2O3/TiO2= 22-48), but Al-depleted komatiites are also reported. The partial melting model for the HREE composition of the Quebra Osso komatiitic melt refers to 50% batch melting of a garnet-free source showing composition similar to pyrolytic mantle. The formation of Quebra Osso komatiite lavas is associated with the ascension of a mantle plume, subsequently erupted onto the sialic crust of the Santa Bárbara Complex.